2015
DOI: 10.1007/s00415-015-7867-4
|View full text |Cite
|
Sign up to set email alerts
|

The full spectrum of ethical issues in the care of patients with ALS: a systematic qualitative review

Abstract: Dealing systematically with ethical issues in amyotrophic lateral sclerosis (ALS) care requires an unbiased awareness of all the relevant ethical issues. The aim of the study was to determine systematically and transparently the full spectrum of ethical issues in ALS care. We conducted a systematic review in Medline and Google Books (restricted to English and German literature published between 1993 and 2014). We applied qualitative text analysis and normative analysis to categorise the spectrum of ethical iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
(80 reference statements)
0
20
0
Order By: Relevance
“…Being a relentlessly fatal disease with no curative therapy currently available, there are many ethical issues in ALS care, from the diagnosis to the latest stages of disease, as recently reviewed [ 172 ]. End-of-life discussions, including gastrostomy, NIV and invasive mechanical ventilation are often delayed, potentially leading to unplanned crisis interventions [ 173 ].…”
Section: Ethical Issues In Motor Neuron Diseasementioning
confidence: 99%
“…Being a relentlessly fatal disease with no curative therapy currently available, there are many ethical issues in ALS care, from the diagnosis to the latest stages of disease, as recently reviewed [ 172 ]. End-of-life discussions, including gastrostomy, NIV and invasive mechanical ventilation are often delayed, potentially leading to unplanned crisis interventions [ 173 ].…”
Section: Ethical Issues In Motor Neuron Diseasementioning
confidence: 99%
“…We could thereby ground the analysis in the practical reality of those working in the field. Our review is furthermore different from other reviews of ethical issues [18, 28] in that it also extracted proposed strategies to adequately deal with ethical issues identified, although we only present our findings on the issue of informed consent. From the standpoint of guideline developers, this broader perspective seems desirable as it allows formulating recommendations regarding how to handle diverse issues knowing all arguments put forward in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, we had good reasons for choosing an approach based on principlism. Most importantly, other systematic qualitative reviews of normative information already demonstrated the instrumental value of this approach for a descriptive and stakeholder-oriented analysis and synthesis of normative arguments [18, 19, 28]. Additionally, we found this approach to be more grounded in the actual theoretical discussions in the public health ethics literature than, for example, an approach relying on the authors’ statement in the abstract to discuss ethical issues (which other reviews relied on [48]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing body of research on the field of ethical challenges in healthcare 1 e.g. in the care of patients with ALS (Seitzer et al 2016 ), in elderly and dementia care (Hasselkus 1997 ; Van der Dam 2011 ; Bolmsjö et al 2006 ), in long-term care (Elander et al 1993 ), and in (community) mental healthcare (Liégeois and Van Audenhove 2005 ; Molewijk et al 2008a , b , 2015 ). Most ethical challenges are related to quality of care and quality of the organization of health care institutions.…”
Section: Introductionmentioning
confidence: 99%